Influence of molar fraction of Mg/Al, on the electrochemical behavior of hycrotalcite-epoxy-graphite composites - Balbin Tamayo, Abel; Esteva Guas, Ana Margarita; Pupim Ferreira, Antonio A. [UNESP]; Aucelio, Ricardo Q.; Huertas Flores, Jhonny O. (Elsevier B.V., 2020)
The layered structure of hydrotalcite-like compounds is responsible for many chemical and physical properties attractive in designing electrodes for analytical applications. Mg/Al hydrotalcite-like materials were prepared with different Mg/Al molar ratios ranging from 1.5:1 to 6:1 and electrochemically characterized before being included into epoxy-graphite to form the electrode matrix. The electrochemical response of the electrodes was evaluated by the use of potassium ferro/ferricyanide redox pair as a probe for voltammetry and impedance spectroscopy. The electm-catalytic effect on the potassium ferm/ferricyanide redox pair showed was more effective when Mg and Al is 1.5:/1 M proportion due, apparently, to the more positively charged hydrotalcite layers and more affinity for anions such as Fe(CN)(6)(3-/4-). This epoxy-graphite-hydrotalcite composite presents the lowest potential difference and lowest loading transfer resistance associated with the hydrotalcite phase, which are desirable properties for potential electroanalytical purposes. The results indicated the potential application of the epoxy-graphite-hydrotalcite electrode for ion exchange of negative-charged chemical species.
Keywords: Characterized; Epoxy-graphite-hydrotalcite; Electro-catalysis; Modified electrodes